1993
DOI: 10.1001/archinte.153.8.957
|View full text |Cite
|
Sign up to set email alerts
|

'Subclinical hypothyroidism'. Natural course of the syndrome during a prolonged follow-up study

Abstract: "Subclinical hypothyroidism" is not always a forerunner of primary hypothyroidism. Two distinct populations evolve: (1) those with true preclinical or subclinical hypothyroidism, which may be predicted by the presence of one of the well-known etiologic factors responsible for onset of primary hypothyroidism, and (2) euthyroidism with reset thyrostat--a permanent state without a definitive progression to hypothyroidism, most probably secondary to a previous subtle insult to the thyroid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 25 publications
1
46
0
3
Order By: Relevance
“…The TSH change was smaller in this group; it is therefore possible that if the observation period were longer, an analogous change would have been observed in this group too. Some individuals with elevated TSH do not lower their cholesterol levels after treatment with T 4 indicating that there may exist two different kinds of patients in this group, as proposed by Kabadi (20), the non-responders probably corresponding to those with a 'reset thyrostat' (20) and the responders having true subclinical disease. These individuals may be recognised using the criteria mentioned above.…”
Section: Journal Of Endocrinology (1998) 138mentioning
confidence: 83%
“…The TSH change was smaller in this group; it is therefore possible that if the observation period were longer, an analogous change would have been observed in this group too. Some individuals with elevated TSH do not lower their cholesterol levels after treatment with T 4 indicating that there may exist two different kinds of patients in this group, as proposed by Kabadi (20), the non-responders probably corresponding to those with a 'reset thyrostat' (20) and the responders having true subclinical disease. These individuals may be recognised using the criteria mentioned above.…”
Section: Journal Of Endocrinology (1998) 138mentioning
confidence: 83%
“…With respect to the previous studies on young (3)(4)(5)(6)(7) or old patients (11)(12)(13)(14), our study design is peculiar, in that we have preliminarily excluded all the underlying diseases and the risk factors that are known to be able to affect the natural course of SH (3-7). According to our results, the natural history of TSH serum levels in a pediatric population with idiopathic SH is characterized by their progressive decrease over time, with no concomitant changes in FT 4 values.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have carried out follow-up studies on patients with SH (10,(22)(23)(24)(25)(26), but none of these studies used as short and regular control intervals as the present study. Four-year follow-up of SH patients from the Wickham study showed that 8 out of 48 developed OH.…”
Section: Discussionmentioning
confidence: 99%